Creative-based strategies in small and medium-sized cities: Key dimensions of analysis - Selada, Catarina; Cunha, Inês Vilhena da; Tomaz, Elisabete (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2012)
The present article intends to contribute to the literature and research agenda regarding the importance of the creative economy as a driver for the revitalisation and development of small and medium-sized cities in Europe. Several studies argue that these territorial areas are necessarily doomed to failure and decline due to the lack of critical mass and density in terms of economic and institutional resources. However, some small towns are changing their development path towards a new ‘urban’ paradigm. The present research aims to identify and analyse a set of dimensions that have to be taken into consideration in the implementation of creative-based strategies in small and medium-sized cities, namely: governance factors, endogenous factors, and territorial embeddedness.
Keywords: small and medium-sized cities; creative economy; creative-based strategies; local development